Improving the thermal performance and resilience of Myanmar housing in a changing climate - Zune, May (2021)
Despite the long-term climate risk index for the period 1990-2018, there is a dearth of research and understanding of the vulnerability of homes to overheating in Myanmar. This thesis adopted a “case study research method with multiple cases” and addressed concerns about climate change impacts on Myanmar housing, particularly for the thermal performance of detached houses, which comprise the primary housing type in Myanmar. In order to fill the research gap in Myanmar Sustainable Development Plan and the Myanmar Building Code, four objectives were structured for the scope of this thesis: (1) lessons learnt from Myanmar vernacular architecture; (2) an investigation of the impacts of climate change and overheating risks in Myanmar housing; (3) an investigation of the impacts of the Passivhaus’ fabric-first approach on the Myanmar contexts; and (4) a review of barriers, challenges, and limitations of adopting the Passivhaus’ fabric-first approach in Myanmar.